2019
DOI: 10.1002/pmrj.12127
|View full text |Cite
|
Sign up to set email alerts
|

Team‐Based Medicine: Incorporating a Clinical Pharmacist into Pain and Opioid Practice Management

Abstract: Background The Centers for Disease Control and Prevention (CDC) reports that death from opioids has increased by more than five times since 1999. In response, federal and state organizations have released guidelines recommending best practice standards to combat the opioid epidemic. Objective To evaluate the impact of a clinical pharmacist in a team‐based care model on the adherence to best practice standards and access to care for management of patients prescribed chronic opioid therapy (COT). Design Retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 11 publications
0
33
0
Order By: Relevance
“…Besides technology‐based interventions, also ward‐based pharmacy and multi‐disciplinary team‐based interventions can contribute to improved pain management (Boren et al., 2019; Mathew et al., 2016; Poirier et al., 2019; Semerjian et al., 2019). Conversely, many of these interventions are frequently time consuming, less efficient to realize on a hospital‐wide basis and cannot be provided continuously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides technology‐based interventions, also ward‐based pharmacy and multi‐disciplinary team‐based interventions can contribute to improved pain management (Boren et al., 2019; Mathew et al., 2016; Poirier et al., 2019; Semerjian et al., 2019). Conversely, many of these interventions are frequently time consuming, less efficient to realize on a hospital‐wide basis and cannot be provided continuously.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacy services might be valuable in this regard (Krähenbühl‐Melcher et al., 2007). Studies have already shown that the integration of pharmacists into pain management teams can improve overall pain therapy (Boren et al., 2019; Mathew et al., 2016). For example, Poirier et al showed that a pharmacist‐led pain management service resulted in decreased opioid use (Poirier et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies were judged to be of average quality. Two of the studies were judged to have a serious risk of bias, 21,26 five moderate, [22][23][24][25]27 and only one low risk of bias. 28 The studies were judged to have a serious risk of bias due to participant selection and confounding (Table S2).…”
Section: Observational Studiesmentioning
confidence: 99%
“…We also identified five studies where pharmacists were involved in the multidisciplinary or interdisciplinary team for the management of pain. 16,21,[23][24][25] Pharmacists reviewed patient medications, 16 performed opiate stewardship, where they screened and evaluated the use of opioids to support its judicious use, 21,23,24 and provided patient education. 25 These approaches led to improvements in pain score, 16 pain disability index, 24 symptoms of anxiety and depression, [23][24][25] selfefficacy, 25 pain severity and interference, as well as reduced need for morphine use 21,23 (Table 4).…”
Section: Multidisciplinary Team For the Management Of Painmentioning
confidence: 99%
See 1 more Smart Citation